PERSEPSI MASYARAKAT TERHADAP PENGAJUAN PERHUTANAN SOSIAL SKEMA HUTAN DESA DI KAMPUNG KUADAS KECAMATAN MAKBON KABUPATEN SORONG - Serkadifat, Yetty; Loppies, Yerrynaldo; Patty, Ningsih Damaris M; Tuhumena, Lolita Constantia; Wambrauw, Daniel Z. K (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2024)
Background : Kuadas Village, located in Sorong Regency, is one of the villages selected by the Forest Area Management (KPH) of Sorong Regency through the Social Forestry Indicative Map (PIAPS) created by the Social Forestry and Environmental Partnership Center (BPSKL). It is proposed under the social forestry program with a village forest scheme and is currently facilitated by the NGO (Non-Governmental Organization) Fauna Flora Indonesia Program in the submission of the Social Forestry Village Forest Scheme. However, the issues faced by the surrounding village communities are usually related to social and economic aspects in managing the forest. Method: The researcher used 46 respondents as samples and conducted the study from June to July 2023 in Kuadas Village, Makbon District, Sorong Regency, using the Saturated Sampling technique. The data obtained were analyzed using the Likert Scale. Results: Three perception aspects were assessed, namely the Utilization and Level of Dependence on Forest Resources, Forest Sustainability, and Perception of Social Forestry. After calculating with the Likert Scale formula, it was found that the aspect of Social Forestry Perception received the highest score with a total of 1.175 and a percentage of 87.7%. Conclusion: The development of knowledge about community perceptions regarding the submission of the Social Forestry Village Forest Scheme can provide valuable information for readers, such as the village or others.